Vaccination coverage survey by social stratum in children up to 24 months of age in Londrina, Paraná, Brazil, between 2021 and 2022 - Edmilson de Oliveira; José Cássio de Moraes; Ana Paula França; Adriana Ilha da Silva; Alberto Novaes Ramos Jr; Ana Paula França; Andrea de Nazaré Marvão Oliveira; Antonio Fernando Boing; Carla Magda Allan Santos Domingues; Consuelo Silva de Oliveira; Ethel Leonor Noia Maciel; Ione Aquemi Guibu; et al. (Ministério da Saúde do Brasil, 2024)
ABSTRACT Objective To analyze vaccination coverage according to social strata in children up to 24 months old, living in the municipality of Londrina (PR), Brazil. Methods This was a population-based survey conducted between 2021 and 2022, in which vaccination coverage and sociodemographic aspects of mothers and families were evaluated using Pearson's chi-square test. Results In a sample of 456 children, complete vaccination coverage varied according to social strata, being 36.0% (95%CI 26.8;57.8); in stratum A; 59.5% (95%CI 26.1;86); in stratum B; 66.2% (95%CI 51.7;78.1); in stratum C; and 70.0% (95%CI 56.1;81.0) in stratum D. Conclusion The analysis of vaccination coverage indicated that social stratum A is at highest risk for vaccine-preventable diseases.